Сказка о том, как птицы царя выбирали: Стихи и сказки / М. Е. Кильчичаков ; худож. В. И. Олефиренко ; перевод с хакасского: Я. Козловский, В. Семенов, Г. Сысолятин - Кильчичаков Михаил Еремеевич (Советская Россия, 1987)
Экземпляры: ф. 11 (20211118) / Инвентарный номер: 17087 / Цена: 0.10 / Авт.знак: К 39 / ББК: 84(2Рос.Хак)-45